The Research of the Growth and Competitiveness of Industrial Companies - Valentinavičius, Stasys (Ekonomika, 2003)
The main object of this work is process of growth and competitiveness of company. The essential point to analyse methods of the evaluation of growth of company, to determinate possibilities and tools to manage process of growth and competitiveness. That could be helpful to potential investor or owner of capital to estimate alternatives of investment. Evaluation methods and parameters, the exhaustive financial estimation of growth of company creating economical value added (EVA) were analysed.The exhaustive research of Lithuanian joint stock companies was made. The practical example of evaluation of growth of one company by various growth rates was made for more detailed analysis. Research led to conclusion, that Lithuanian companies should be directed to increase competitiveness based on the creation economic value (EVA). To encourage growth of companies strategic recommendations were created and tools for EVA enlargement and management system were suggested.